Postoperative tibial plateau angle changes and their influence on ground reaction forces 6 months after TPLO: a prospective study - Volz, Frederik; Eberle, Daniela; Kornmayer, Matthias; Klever, Julius; Meyer-Lindenberg, Andrea (Frontiers in Veterinary Science, 2025)
ObjectivesThe objectives of the study were to investigate the association between change in postoperative (post-op) tibial plateau angle (TPA) in dogs and cranial cruciate ligament disease (CCLD) after tibial plateau leveling osteotomy (TPLO) during 6 months on the post-op outcome.MethodsThe inclusion criteria included 60 dogs with CCLD treated with TPLO fulfilled. TPA measurements were taken immediately post-op and 6 months post-op by three observers, and change in TPA was calculated. The outcome was evaluated using lameness score, owner questionnaire, and gait analysis performed preoperatively and 6 months post-op.ResultsThe mean change in TPA was 0.22 ± 0.75°. The interobserver reliability for TPA measurements was excellent. No differences in TPA measurements between observers were found (p = 0.07–0.105). No association between the change in TPA and outcome was found. The multivariate linear regression model for the symmetry index of peak vertical force (SIPVF) 6 months post-op was significant (R2 = 0.210; p = 0.031), and the TPA at 6 months post-op was the only significant factor (ß = 0.459; 95% CI: 0.41–1.44; p < 0.001), indicating that a lower TPA 6 months post-op results in lower SIPVF values.ConclusionThe study indicated that lower TPAs 6 months post-op lead to a more symmetrical gait in hindlimbs 6 months post-op. No other significant factor between post-op changes in TPA and outcome after TPLO was found. Our results showed little post-op TPA change up to 6 months. This indicates that change in TPA is not present as reported.